POLA MAKAN DAN KADAR ASAM URATPADA WANITA MENOPAUSE YANG MENDERITA GOUT ARTHRITIS DIPUSKESMAS TIKALA BARUMANADO - Rudolf B. Purba; Fred Rumagit; Novita P. Loleh (Jurnal GIZIDO, 2015)
Arthritis Gout is a metabolic disease characterized by deposition of urate in the joints ofarthritis that was painful. One of the factors that can affect is the food consumed and therisk increases in women after menopause. The aim of research to determine therelationship of diet with high levels of uric acid in postmenopausal women who suffer fromgout arthritis in Tikala Baru health center.Sort of observational research using crosssectional design. Primary data was collected through interviews and observation usingquestionnaires, secondary data taken from health centers. Of the 39 respondents oftenconsume types of foods containing purine source'm ie chicken, fish, spinach, tempe, tofu,spinach and beans. Frequency of purine food source for the highest weekly thatconsumes 3x per week in which there were 14 (35.9%). Protein intake more there were34 people (87.2%) and purine intake were 5 people (12.8%). There is a significantrelationship between the frequency of consuming food containing sources of purinesbeing per week with uric acid levels (ρ <0:01) in postmenopausal women at healthcenters Tikala Baru Manado and there was no correlation between the characteristics ofthe study subjects (intake of protein, and purine) with uric acid levels